2006
DOI: 10.1097/01.prs.0000220473.94654.a4
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction in Older Women: Should Age Be an Exclusion Criterion?

Abstract: The authors believe that all types of reconstruction should be an option for women older than 60 years of age and that age as an isolated factor should not deter physicians from offering these women the option of breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 22 publications
4
43
0
2
Order By: Relevance
“…In particular, capsular contracture is specific to implant-based reconstruction, whereas abdominal donor-site complications (e.g., hernia, contour abnormalities, trunk function, and anastomotic complications at the recipient site) are specific to abdominal flap reconstruction. Seven studies 9,13,16,17,26,27,30 reported on capsular contracture, although only one specified the use of the Baker system in classifying this complication. 30 Rates of capsular contracture following tissue expander/implant reconstruction ranged from 0.0 to 33.3 percent (Table 3).…”
Section: Method-specific Complicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, capsular contracture is specific to implant-based reconstruction, whereas abdominal donor-site complications (e.g., hernia, contour abnormalities, trunk function, and anastomotic complications at the recipient site) are specific to abdominal flap reconstruction. Seven studies 9,13,16,17,26,27,30 reported on capsular contracture, although only one specified the use of the Baker system in classifying this complication. 30 Rates of capsular contracture following tissue expander/implant reconstruction ranged from 0.0 to 33.3 percent (Table 3).…”
Section: Method-specific Complicationsmentioning
confidence: 98%
“…Only a single study also evaluated other abdominal flaps (i.e., DIEP and SIEA flap reconstruction). 17 All were cohort trials, mostly conducted in North America (n = 11), 9,13,14,17,18,[24][25][26][27][28][29] with one each from Croatia/Austria, 15 Italy, 30 and the United Kingdom. 16 The mean follow-up period ranged from 6 months 15 to 60.2 months 18 ( Table 2).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…This influence of physician bias has been demonstrated in breast cancer, prostate cancer and head and neck cancer [10,11,12,13]. It is unclear how physician selection operates to influence actual treatment outcome in head and neck cancer, which prompted us to conduct this retrospective survey.…”
Section: Introductionmentioning
confidence: 99%
“…Die von den Patienten auch in höherem Lebensalter erwarteten Ergebnisse plastisch-rekonstruktiver Eingriffe, wie z. B. die Brustrekonstruktion, kann bei der Gruppe der über 60-Jährigen jedoch eine notwendige sekundäre Korrekturrate von bis zu 20,5% erreichen [9]. Zwar ist hohes Lebensalter über 70 Jahren per se noch nicht mit einer erhöhten eingriffsspezifischen Komplikationsrate wie z.…”
Section: Patientengruppenunclassified